The impact of internal marketing on the organisational culture of ppes works (Sarawak) Sdn Bhd/ Muriyadi Basri - Basri, Muriyadi (2007)
The research is to determine the level of related internal marketing variables which might have significant effect on the organizational culture of PPES Works. The research also aimed to find the association between the internal marketing variables and the change in the organizational culture of PPES Works. The result of the study reveals that there is significant association between the level of the internal marketing variables and the change in the organizational culture of PPES Works.